Severe fever with thrombocytopenia syndrome with myocardial dysfunction and encephalopathy: A case report. Issue 9 (September 2016) - Kawaguchi, Takeshi; Matsuda, Motohiro; Takajo, Ichiro; Kawano, Ayako; Kariya, Yumi; Kubo, Kazuyoshi; Miyauchi, Syunichi; Umekita, Kunihiko; Nagatomo, Yasuhiro; Yano, Takao; Yano, Kouji; Okayama, Akihiko
Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging infectious disease in China, Korea and Japan caused by a novel bunyavirus, SFTS virus (SFTSV). Although central nervous system manifestations are common in SFTS patients, the pathogenesis has not been elucidated; and there are few reports of myocardial dysfunction. Here we report an elderly Japanese patient with reversible myocardial dysfunction and encephalopathy. A previously healthy 65-year-old male engaged in forestry got a tick bite and developed fever and fatigue in 3 days. Three days after onset, he presented to a local hospital where the diagnosis of SFTS with hemophagocytotic syndrome was made. The blood test showed leukopenia and thrombocytopenia as well as elevated levels of alanine aminotransferase and aspartate aminotransferase. Marked hemophagocytosis was found on bone marrow smear. Peripheral blood was positive for SFTSV gene by reverse-transcription polymerase chain reaction. On day 7, the patient was transferred to our hospital. We observed disturbance of consciousness, Kernig sign and myoclonus to face and limbs. Decreased blood flow of whole cerebral cortex was detected by single photon emission computed tomography (SPECT). Chest X-ray revealed cardiomegaly and electrocardiography (ECG) showed abnormal T waves. These data suggested acute encephalopathy and myocardial dysfunction. We treated him with corticosteroid and blood transfusion, which resulted in the complete recovery of the above abnormal symptoms and laboratory data including the findings in SPECT and ECG in about a month. This case demonstrated transient myocardial dysfunction and encephalopathy can occur in addition to typical clinical manifestation of SFTS.